Review of Vangelis Karamanolakis, Ανεπιθύμητο παρελθόν: Οι φάκελοι κοινωνικών φρονημάτων στον 20ό αιώνα και η καταστροφή τους [Unwanted past: The files on social beliefs in the 20th century and their destruction] - Karpozilos, Kostis (Historein, 2024)
Review of Vangelis Karamanolakis, Ανεπιθύμητο παρελθόν: Οι φάκελοι κοινωνικών φρονημάτων στον 20ό αιώνα και η καταστροφή τους [Unwanted past: The files on social beliefs in the 20th century and their destruction]. Athens: Themelio, 2019. 319 pp.